2003
DOI: 10.1242/dev.00517
|View full text |Cite
|
Sign up to set email alerts
|

Gata factor Pannier is required to establish competence for heart progenitor formation

Abstract: Inductive signaling is of pivotal importance for developmental patterns to form. In Drosophila, the transfer of TGFβ (Dpp) and Wnt (Wg) signaling information from the ectoderm to the underlying mesoderm induces cardiacspecific differentiation in the presence of Tinman, a mesoderm-specific homeobox transcription factor. We present evidence that the Gata transcription factor, Pannier, and its binding partner U-shaped, also a zincfinger protein, cooperate in the process of heart development. Loss-of-function and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 99 publications
4
88
0
Order By: Relevance
“…Pnr augments ectopic Tin-induced dSUR expression, as it does with Dmef-2 and dHand (12,14,32), but the Pnr consensus sites in the cardiac enhancer do not seem to be required. Nevertheless, Tin and Pnr act synergistically in activating dSUR both in vitro and in vivo, and forced expression of tin is unable to restore dSUR expression in flies expressing dominant-negative pnr-EnR.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Pnr augments ectopic Tin-induced dSUR expression, as it does with Dmef-2 and dHand (12,14,32), but the Pnr consensus sites in the cardiac enhancer do not seem to be required. Nevertheless, Tin and Pnr act synergistically in activating dSUR both in vitro and in vivo, and forced expression of tin is unable to restore dSUR expression in flies expressing dominant-negative pnr-EnR.…”
Section: Discussionmentioning
confidence: 93%
“…Whole-mount in situ hybridization was performed as described in ref. 32. Primer sequences for cloning dSUR enhancer fragments, generation of UAS-dSUR-RNAi transgenic flies, and quantitative RT-PCR (Roche) are described in Supporting Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, an amorph allele of emc (Brown et al 1995); Bar 1 (B 1 )/FM7, a dominant gain-offunction mutation generated by duplication of the 16A region containing BarH1 and BarH2 genes, referred to as Bar (B); Df(1)Bar , a deficiency in which both B genes are deleted (Higashijima et al 1992); sgg 1 /FM7a Dp(1;2;4) w 1 , a lethal recessive X-ray allele of sgg (Bourouis et al 1990); Df (2L) BSC7/CyO, UAS-pnr D4 (Haenlin et al 1997); y w; FRT82, pnr vx6 / TM6B (Heitzler et al 1996); UAS-pnr ENR , a dominant-negative form of pnr, which contains the repressor domain from Engrailed (amino acids 2-298) (Klinedinst and Bodmer 2003); UAS-ush (Fossett et al 2001); Df (3L) Iro-C DFM3 FRT80/TM6B, a deficiency for ara, caup, and promoter for mirr, UAS-ara (Gomez-Skarmeta et al 1996); UAS-mirr (McNeill et al 1997); y w ey-FLP (Newsome et al 2000); and pnr-GAL4 . All stocks are described in FlyBase (http:/ /flybase.bio.indiana.edu).…”
mentioning
confidence: 99%
“…Recent studies of genes involved in heart development (5, 6) have revealed discrete subsets of cardioblasts and pericardial cells. According to the expression domains of heart identity genes, in each abdominal segment three types of cardioblasts can be detected, the anterior tinman (tin)-expressing pair, the adjacent tin͞ladybird (lb)-positive pair, and the most posterior seven up (svp)-expressing pair (5)(6)(7)(8)(9)(10). As for pericardial cells, the combinatory code of tin, lb, even-skipped (eve), and odd-skipped (odd) expression makes it possible to distinguish five distinct subpopulations (6-8, 10, 11).…”
mentioning
confidence: 99%